Assessing Rural Water Quality: comparing improved and unimproved drinking water sources in Hawul LGA - Joshua, Williams (Creative Science, 2021)
Rural water quality has been identified as an issue in most developing countries due to the large- scale agricultural activities and presence of industries. These in addition to poor or lack of water treatment facilities exposes rural water sources to contamination. This study analysed the suitability of water sources for drinking within rural settlements in Hawul LGA. Water sources from streams, open hand-dug wells, hand-pumped boreholes, and electrically operated boreholes were collected and analysed for physical, chemical, and bacteriological contaminants. Parameters were analysed using standard laboratory procedures. Water sources were grouped into improved (boreholes) and unimproved (stream and open wells) water sources and analysed using t-Test statistical method to infer if the mean of parameters were statistically greater than the NIS standard guidelines for drinking water. The results indicate that 39.50% of water from unimproved water sources failed to conform to the NIS standards and constitutes to the likelihood of health-related impacts especially water sources from the stream. Stream water sources with mean values 19TCU (colour), 24.70 NTU (turbidity), 92.60 mg L–1 (nitrate), 37.90 mg L–1 (magnesium), 0.30 mg L–1 (lead), 0.30 mg L–1 (manganese), 4.10 mg L–1 (potassium), 0.90 mg L–1 (phosphate), 186.70 mg L–1 (hardness), 4.70 cfu mL–1 (coliform count), and 1.70 cfu mL–1 (E. coli) are all significantly greater than the respective values stipulated by the NIS. However, only manganese and coliform count from hand-operated boreholes (Improved water sources) were found to exceed the stipulated standards. This indicates that only 5.30% of water from improved water sources failed to meet standards. More so, all water samples from electrically operated boreholes adhered to the NIS stipulated guidelines. The results shows that there is a low risk to health associated with water from improved water sources but there is a likelihood of health-related issues associated with water from unimproved sources due to the high values from chemical and bacteriological contaminants.